Розрахунок ефективності механизму державно-корпоративного партнерства - Мурзабулатова, О. В. (ХНУРЭ, 2015)
The preparation phase includes the development of the project concept, the passport of the project, preparation of contract and other documentation, research, competition procedures, including the selection of consultants and other contractors for the purposes of the project implementation
Keywords: державно-корпоративне партнерство; механизм державно-корпоративного партнерства